2021
DOI: 10.1177/23259671211021577
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bioabsorbable and Metallic Interference Screws for Graft Fixation During ACL Reconstruction: A Meta-analysis of Randomized Controlled Trials

Abstract: Background: Bioabsorbable interference screws and metallic interference screws are both widely used for graft fixation, but it remains unclear which screw type is superior. Purpose: To compare clinical outcomes and complications between bioabsorbable and metallic interference screws for anterior cruciate ligament reconstruction (ACLR). Study Design: Systematic review; Level of evidence, 1. Methods: The literature was searched for relevant randomized controlled trials published between 1966 and 2020. Two invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Anchoring the reconstructed graft to the bone may be achieved by different devices such as screws, buttons, cross pins and screw posts or a combination of these on the femoral side [20] . Bioabsorbable and metallic screws are both frequently used for femoral or tibial fixation in ALC reconstructions and a recent meta-analysis showed that although there is no difference between them in terms of subjective knee function or knee laxity, bioabsorbable screws may show more complications [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Anchoring the reconstructed graft to the bone may be achieved by different devices such as screws, buttons, cross pins and screw posts or a combination of these on the femoral side [20] . Bioabsorbable and metallic screws are both frequently used for femoral or tibial fixation in ALC reconstructions and a recent meta-analysis showed that although there is no difference between them in terms of subjective knee function or knee laxity, bioabsorbable screws may show more complications [21] .…”
Section: Discussionmentioning
confidence: 99%
“…As a downside, it interferes with magnetic resonance imaging (MRI) and has to be removed during revision surgery ( Emond et al, 2011 ). With the development of biomaterials, bioabsorbable interference screws have been introduced to the clinic, with some patients preferring the clinical outcome of the screw disappearing ( Xu et al, 2021 ). Most current metal interference screws are composed of titanium, but bioabsorbable interference screws are composed of a variety of biodegradable biomaterials that are non-toxic, non-responsive to tissue, and degrade over time ( Xu et al, 2021 ).…”
Section: Factors That May Influence Tendon-bone Healing Of the Acl Re...mentioning
confidence: 99%
“…With the development of biomaterials, bioabsorbable interference screws have been introduced to the clinic, with some patients preferring the clinical outcome of the screw disappearing ( Xu et al, 2021 ). Most current metal interference screws are composed of titanium, but bioabsorbable interference screws are composed of a variety of biodegradable biomaterials that are non-toxic, non-responsive to tissue, and degrade over time ( Xu et al, 2021 ). However, there have been some clinical reports of adverse reactions related to bioabsorbable interference screws, such as the risk of synovitis, excessive inflammation, and tunnel widening ( Xu et al, 2021 ).…”
Section: Factors That May Influence Tendon-bone Healing Of the Acl Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…The other is suspensory fixation like EndoButton ® (Smith & Nephew, Inc. Andover, MA, USA). Metallic interference screws (MISs) were the first applied interference screw that have reached a reliably positive clinical outcome ( 8 ). MISs can promote early bone integration with high initial fixation strength but a relatively high failure load which is very difficult to remove during revision surgery ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%